An Effective Approach for Sarcasm Detection in Text Data for Sentimental Analysis - M J, Adarsh; Pushpa Ravikumar, Dr. (International Journal of Engineering and Technology, 2018)
The stream of Sentiment Analysis has become very popular today helping people and corporate to analyze the orientation of sentiments towards particular product and people. The Sentiment Analysis will not be complete without analyzing the Sarcasm or Irony in statements. Sarcasm is the art of saying something opposite to the original meaning in a sentence. Most of the times Sarcasm in sentences makes it more Negative than positive. In this paper, an approach is adopted to identify the sarcasm in sentences using Sentiwordnet. A set of core popular sarcastic sentences are considered and scores are calculated. The scores points out at the sarcasm in sentences which most of the time is negative. The polarities of sentences are also calculated and also the sentences are checked for sarcasm scores in Sarcasm detector tool.Â Â